Notifiche
Cancella tutti

espressioni con frazioni generatrici

  

0
IMG 9753
Autore
2 Risposte



2
IMG 6412



0
image

=============================================================

$\small  \left(12,\overline{57}-9,\overline{34}+0,\overline{49}\right) : 0,\overline{81}-\left(1,\overline3+0,\overline6\right)=$

$\small = \left(\dfrac{1257-12}{99}-\dfrac{934-9}{99}+\dfrac{49-0}{99}\right) : \dfrac{81-0}{99}-\left(\dfrac{13-1}{9}+\dfrac{6-0}{9}\right)=$

$\small = \left(\dfrac{1245}{99}-\dfrac{925}{99}+\dfrac{49}{99}\right) : \dfrac{\cancel{81}^9}{\cancel{99}_{11}}-\left(\dfrac{\cancel{12}^4}{\cancel9_3}+\dfrac{\cancel6^2}{\cancel9_3}\right)=$

$\small = \dfrac{\cancel{369}^{41}}{\cancel{99}_{11}}·\dfrac{11}{9}-\left(\dfrac{4}{3}+\dfrac{2}{3}\right)=$

$\small = \dfrac{41}{\cancel{11}_1}·\dfrac{\cancel{11}^1}{9}-\dfrac{\cancel6^2}{\cancel3_1}=$

$\small = 41·\dfrac{1}{9}-2=$

$\small = \dfrac{41}{9}-2=$

$\small = \dfrac{41-18}{9}= \dfrac{23}{9}$



Risposta
SOS Matematica

4.6
SCARICA